Participants' perceptions of motivation, randomisation and withdrawal in a randomised controlled trial of interventions for prevention of depression. Issue 12 (30th November 2009) - Grant, J Busby; Mackinnon, A J; Christensen, H; Walker, J
Abstract : Aims and background: Little is known about how participants perceive prevention trials, particularly trials designed to prevent mental illness. This study examined participants' motives for participating in a trial and their views of randomisation and the ability to withdraw from a randomised controlled trial (RCT) for prevention of depression. Methods: Participants were older adults reporting elevated depression symptoms (N = 900) living in urban and regional locations in Australia who had consented to participate in an RCT of interventions to prevent depression. Participants rated their agreement with various statements describing motivations for enrolment in the trial and opinions regarding randomisation and withdrawal. Results: The majority of participants expressed a triad of altruistic motivation for participation, relative lack of concern about randomisation and commitment to the trial. Certain subgroups of participants, such as women and those with higher depression scores, reported higher levels of concern about specific issues. Conclusions: The findings suggest that participants enrolled in prevention trials for mental illness are likely to hold positive attitudes (eg, high commitment, low expectation of personal gain) towards research trials. The identification of relationships between key person factors and trial-related attitudes enabled profiling of participant groups, which can inform recruitment strategies and interactions of participants and research projects in future prevention trials.